No justice, no peace prize: Stanley "Tookie" Williams, the 1992 Bloods‐Crips truce, and the limits of racial peacekeeping. (15th October 2021) - Vaught, Seneca
Abstract: This study examines the life of Crips cofounder Stanley "Tookie" Williams and the controversy surrounding his multiple nominations for the Nobel Peace Prize. After being sentenced to death for a quadruple murder, Williams underwent a period of radical transformation and became an internationally recognized ambassador for peace. From San Quentin's death row, Williams supported several internationally recognized gang peace initiatives including the 1992 Watts truce, the 1993 Summit on Urban Peace and Justice, Hands Across America, and the 2004 Tookie Protocol for Peace. This article explores the challenges Williams faced in his evolution from a gang member to a peace activist, his role in these projects, and how neoliberal criminal justice reforms undermined his global efforts to promote grassroots peace coalitions.